An autopsy case of suspected anti-N-methyl-D-aspartate receptor encephalitis - Kino Hayashi; Wakako Hikiji; Yohsuke Makino; Hisaomi Suzuki (Wolters Kluwer Medknow Publications, 2019)
N-methyl-D-aspartate receptor (NMDAR) encephalitis is a rare type of autoimmune limbic encephalitis. Herein, we report an autopsy case of highly suspected anti-NMDAR encephalitis, based on the patient's past psychiatric history and autopsy findings of bilateral hippocampal sclerosis and ovarian teratoma. We found that it can be difficult to accurately diagnose autoimmune encephalitis at postmortem forensic autopsy without a case history and background information.